2018
DOI: 10.1111/febs.14424
|View full text |Cite
|
Sign up to set email alerts
|

An ice‐binding and tandem beta‐sandwich domain‐containing protein in Shewanella frigidimarina is a potential new type of ice adhesin

Abstract: Submitted new structure to the Protein Data Bank (PDB: 6BG8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 66 publications
(143 reference statements)
8
53
1
Order By: Relevance
“…Thus, this isoform may exist in the intracellular space or on the cell surface. Recently, several reports have shown the existence of such non‐secreted IBPs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this isoform may exist in the intracellular space or on the cell surface. Recently, several reports have shown the existence of such non‐secreted IBPs .…”
Section: Discussionmentioning
confidence: 99%
“…The extension of the N‐ or C‐terminal sequence has sometimes been observed in several IBPs, suggesting that these regions are mostly variable and not conserved. Although their functions have hardly been clarified, several reports have suggested that such additional sequences are responsible for dimerization or anchoring of the protein to the cell surface . The additional C‐terminal sequences of AnpIBP1a and 1b have electrically opposite features (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other DUF3494‐containing proteins were also found in yeasts, algae, fungi and even archaea from regions that experience cold temperatures. In the last decade, increasing numbers of proteins containing the DUF3494 were demonstrated to bind ice crystals and, hence, were classified as IBPs . The current number of DUF3494 proteins confirmed as IBPs is so large that it raises the question of whether or not there are DUF3494s that do not bind to ice.…”
Section: The Duf3494 Protein Familymentioning
confidence: 99%
“…A) being the most representative (~ 68%). Almost all characterized DUF3494 IBPs exhibit this simple architecture . Generally, single‐DUF3494 IBPs also contain an N‐terminal signal peptide, suggesting that these proteins are secreted into the environment near the cells or accumulate in the membrane .…”
Section: Architecture Of Duf3494 Ibpsmentioning
confidence: 99%
See 1 more Smart Citation